Unemployment insurance and business ownership - Sherpa, Lhakpa; Song, Tao (International Journal of Applied Economics, Finance and Accounting, 2023)
In the United States, self-employed business owners are not entitled to unemployment insurance from the state. This can impact an individual’s choice of occupation when it comes to selecting business ownership. In this paper, we examine the relationship between unemployment insurance benefits and business ownership. Using state-level panel data between 1990 and 2020, we study the effect of unemployment insurance on business ownership in the U.S. Exploiting the changes in laws regarding unemployment insurance and employing an empirical strategy of difference-in-difference, we find that a one percent increase in maximum annual unemployment benefit leads to a decline in business ownership by 0.029 percentage points. We suggest some of the policy implications of this result, particularly those that are related to entrepreneurship and business ownership.